The isochoric thermal conductivity of solid n-alkanes: propane C3H8 - Konstantinov, V.A.; Revyakin, V.P.; Sagan, V.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
The isochoric thermal conductivity of solid propane C3H8 has been investigated on three samples of different densities in the temperature interval from 50 K to the onset of melting. In all the cases the isochoric thermal conductivity exhibits dependences that are weaker than Lµ1/T. The results obtained are compared with those for other representatives of n-alkanes. The experimental data are discussed within a model in which the heat istransported by low-frequency phonons and by "diffusive" modes above the phonon mobility edge.